The Level of Organizational Citizenship Behavior among Faculty Members in Algerian Public Universities from the Academic Leaders’ Perspective. - Chehri, Mina (Jordan Journal of Business Administration, 2019)
The objective of this study is to detect the level of organizational citizenship behavior performance among faculty members from the academic leaders’ perspective in the Algerian public universities, The study is based on the descriptive analytical approach to achieve its objectives. A questionnaire was used to test the validity of the study hypotheses and the (SPSS) program was utilized to analyze data. As for the random sample of the study, it consisted of (100) employees who occupy leadership positions in the Faculties of Economics, Commerce and Administration at the Universities of (Boumerdes) and (Algeria (3(). The findings of this study revealed the presence of a moderate level of organizational citizenship behavior performance among faculty members from the academic leaders’ perspective. The results also confirmed the presence of statistically significant differences at the level of significance (α ≤ 0.05) in the estimations of the respondents regarding the level of practicing organizational citizenship behavior by faculty members attributed only to the personal variable (educational qualification). The remaining variables (gender, age, experience and university) did not record any statistically significant differences. Finally, the researcher presented a set of recommendations that can motivate the presence of organizational citizenship behavior.